Ultrastable and Biocompatible NIR‐II Quantum Dots for Functional Bioimaging. (18th December 2017) - Zebibula, Abudureheman; Alifu, Nuernisha; Xia, Liqun; Sun, Chaowei; Yu, Xiaoming; Xue, Dingwei; Liu, Liwei; Li, Gonghui; Qian, Jun
Abstract: Fluorescence bioimaging in the second near‐infrared spectral region (NIR‐II, 1000–1700 nm) can provide advantages of high spatial resolution and large penetration depth, due to low light scattering. However, NIR‐II fluorophores simultaneously possessing high brightness, good stability, and biocompatibility are very rare. Hydrophobic NIR‐II emissive PbS@CdS quantum dots (QDs) are surface‐functionalized, via a silica and amphiphilic polymer (Pluronic F‐127) dual‐layer coating method. The as‐synthesized PbS@CdS@SiO2 @F‐127 nanoparticles (NPs) are aqueously dispersible and possess a quantum yield of ≈5.79%, which is much larger than those of most existing NIR‐II fluorophores. Thanks to the dual‐layer protection, PbS@CdS@SiO2 @F‐127 NPs show excellent chemical stability in a wide range of pH values. The biocompatibility of PbS@CdS@SiO2 @F‐127 NPs is studied, and the results show that the toxicity of the NPs in vivo could be minimal. PbS@CdS@SiO2 @F‐127 NPs are then utilized for in vivo and real‐time NIR‐II fluorescence microscopic imaging of mouse brain. The architecture of blood vessels is visualized and the imaging depth reaches 950 µm. Furthermore, in vivo NIR‐II fluorescence imaging of gastrointestinal tract is achieved, by perfusing PbS@CdS@SiO2 @F‐127 NPs into mice at a rather low dosage. This work illustrates the potential of ultrastable, biocompatible, and bright NIR‐II QDs in biomedical and clinical applications, which require deep tissue imaging. Abstract : NIR‐II emissive PbS@CdS quantum dots are surface‐functionalized with a dual‐layer coating method. The as‐synthesized PbS@CdS@SiO2 @F‐127 nanoparticles (NPs) are aqueously dispersible, and possess certain brightness. Chemically stable and biocompatible PbS@CdS@SiO2 @F‐127 NPs are utilized for deep tissue (950 µm) in vivo microscopic angiography of the mice brain. Noninvasive and large depth (3–5 mm) gastrointestinal tract imaging with high contrast is achieved.